Integrated glycerol processor and proton exchange membrane fuel cell (PEMFC) systems for stationary applications - Noor Afiqah, Sharifmuddin (2015)
This work presents the performance and efficiency analysis of an integrated glycerol processing and proton exchange membrane fuel cell (PEMFC) system. Glycerol processing as one of the renewable fuel system is employed for hydrogen production. The hydrogen produced from glycerol processing is then fed to the PEMFC system to produce the desired electricity. Here, a PEMFC power generation system composed of two subsystems: fuel reforming and fuel cell stack. A fuel reforming is regarded as a suitable process to produce hydrogen for stationary application of fuel cells because of its high hydrogen yield which subsequently is used to generate electricity through the fuel cell stack by producing a desired power outcome. The system was simulated and optimized into 3 cases. The first one involves the high temperature proton exchange membrane fuel cell (HT-PEMFC) and a glycerol reformer without water gas shift reactor whereas in the second case, a water gas shift reactor is included to improve its overall system efficiency. The third case involves low temperature proton exchange membrane fuel cell (LT-PEMFC) with a glycerol reformer, water gas shift reactor and preferential oxidation reactor. In this study, a direct comparison between the performance of HT-PEMFC and LT-PEMFC systems integrated with a glycerol steam reformer with and without a water gas shift reactor is shown. The target power output of both the HT-PEMFC and LT-PEMFC systems for stationary application is in the range of 1-8 kW, which is sufficient for small household application. Based on result, HT-PEMFC system with water gas shift reactor shows the highest composition of hydrogen that give amount of 80.79% which operates at 1063.15 K and 3 atm with carbon to steam ratio of 2. Compared with HT-PEMFC without water gas shift reactor and LT-PEMFC, both gave 44.76% and 66.26% of hydrogen composition respectively. In term of the system efficiency, it is found that the highest system efficiency is also obtained from HT-PEMFC system with water gas shift reactor followed by LT-PEMFC system and HT-PEMFC system without water gas shift reactor. The highest system efficiency obtained is 59.89% efficiency due to its high energy required to generate for the system.